Choroidal thickness profile in inherited retinal diseases in Indian subjects - Chhablani, Jay (Indian J Ophthalmol, 2015)
PURPOSE: To evaluate changes in choroidal thickness (CT) in inherited retinal diseases and its relationship with age, spherical equivalent, visual acuity, and macular thickness. METHODS: Retrospective analysis of 51 eyes with features of retinal dystrophy of 26 subjects, who underwent enhanced depth imaging using spectral domain (SD) optical coherence tomography (OCT), were included. The CT measurements were made at the fovea and at 5 points with an interval of 500 microns in both directions, nasal and temporal from the fovea and were compared with age-matched healthy subjects. Step-wise regression was used to find the relationship between age, spherical equivalent, best-corrected visual acuity (BCVA), central macular thickness (CMT), and subfoveal CT. RESULTS: Disease distribution was as follows: Stargardt's disease 18 eyes (9 subjects); Best disease 5 eyes (3 subjects); cone-rod dystrophy 26 eyes (13 subjects); and Bietti's crystalline dystrophy 2 eyes (1 subject). Mean subfoveal CT was 266.33 ± 76 microns. On regression analysis, no significant correlation was found between subfoveal CT and any other variable such as age (P = 0.9), gender (P = 0.5), CMT (P = 0.1), spherical equivalent (P = 0.3) and BCVA (P = 0.6). While comparing with age-matched healthy subjects, no significant statistical difference was noted (P < 0.05) among all age groups. CONCLUSION: Our study reports quantitative changes in CT in various common inherited retinal diseases seen in Indian populations. To validate changes in choroid, a longitudinal study with larger sample size is warranted.